2021
DOI: 10.1111/ppl.13407
|View full text |Cite
|
Sign up to set email alerts
|

EkFLS overexpression promotes flavonoid accumulation and abiotic stress tolerance in plant

Abstract: Flavonoids with great medicinal value play an important role in plant individual growth and stress resistance. Flavonol synthetase (FLS) is one of the key enzymes to synthesize flavonoids. However, the role of the FLS gene in flavonoid accumulation and tolerance to abiotic stresses, as well as its mechanism has not yet been investigated systematically in plants. The aim of this research is to evaluate the effect of FLS overexpression on the accumulation of active ingredients and stress resistance inEuphorbia k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…Moreover, compared with WT, the AtSOD and AtPOD enzyme activities of L2, L3, and L6 transgenic plants increased by approximately 19.91% and 15.28% under NaCl stress, and increased by approximately 19.20% and 8.48% under PEG stress, respectively (Figure 9c,d). On the other hand, proline accumulation was used as a physiological index of water shortage in plants [33]. Under NaCl and PEG treatment, the increase in free proline in vivo EkAACT-overexpressing Arabidopsis was lower than that in WT plants (Figure 10), which indicated that EkAACT-overexpressing Arabidopsis has a high-water content.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, compared with WT, the AtSOD and AtPOD enzyme activities of L2, L3, and L6 transgenic plants increased by approximately 19.91% and 15.28% under NaCl stress, and increased by approximately 19.20% and 8.48% under PEG stress, respectively (Figure 9c,d). On the other hand, proline accumulation was used as a physiological index of water shortage in plants [33]. Under NaCl and PEG treatment, the increase in free proline in vivo EkAACT-overexpressing Arabidopsis was lower than that in WT plants (Figure 10), which indicated that EkAACT-overexpressing Arabidopsis has a high-water content.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that plants can activate a series of complex signal transmission networks to resist abiotic stress. This activation can improve tolerance to NaCl and drought stress by increasing SOD and POD enzyme activity to remove excess intracellular reactive oxygen species (ROS), which can inhibit ROS-induced intracellular component oxidation and damage [32,33]. The gene expression and enzyme activity of SOD and POD were measured to investigate whether EkAACT-overexpressing Arabidopsis can promote plant stress resistance to NaCl and drought.…”
Section: Sod and Pod Gene Expression Levels And Enzyme Activities Wer...mentioning
confidence: 99%
See 3 more Smart Citations